UTILISATION OF CUISENAIRE RODS IN ENHANCING MATHEMATICAL ACHIEVEMENT IN FRACTIONS AT THE ELEMENTARY SCHOOL - Fitriyani (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This research aims to enhance the mathematics learning outcomes of fourth-grade students at SD Negeri 042 Kualu Tambang in the Academic Year 2023-2024 through the implementation of the Cuisenaire rod media. The research was conducted through an action research approach with two cycles, involving pre-research activities, observations, and learning outcome tests. The results show that the application of Cuisenaire rod media significantly improves student learning outcomes from 75% in Cycle I to 94% in Cycle II. Despite some notes regarding student inactivity, interview results indicate that students feel interested and joyful during learning with this media. Suggestions put forward include enhancing interactive strategies, varying learning activities, and providing specific training for teachers to optimize the use of Cuisenaire rod media.